Student’s Challenges In Learning English In Boarding School - Harahap, Hilyati Fitria; Andana, Yosi; Aswatdi, Hazhar; Lestari, Sri Dewi; Dewi, Utami (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This case study intended to analyze the high school student's English learning challenges of the boarding school. This study mainly focused on finding students' challenges in learning English. It was conducted in Islamic Centre Sumatera Utara byinvolving 10 students in Islamic boarding school who are also as a santri and a students. The method carried out in this research is a qualitative method, which the research used an analysis in the form of questionnaire that carried out directly in related places. The result from the questionnaires, it could be seen that a half of the respondents found it challenging to learn English and a half did not. And a half ofthe students in the class comprehend the English materials presented by the teacher, and a half of the students may be unsure or uncertain about the materials. And according to the participants or students that participated who filled the questionnaires, said that English lesson is important because English is an international or universal language that needed to make a communication with people abroad and English needed in various sectors like technology development, profession and, education. And also, had trouble because the time in the class for studying English was too short, did not have a basic in English and the way of the teacher delivers the lesson makes students a little difficult in learning English. Referring to these findings, it is suggested that teachers, students and school committees should work together to increase students enthusiasm in learning English.